Chronic Intermittent Hypoxia-Induced Vascular Dysfunction in Rats is Reverted by N-Acetylcysteine Supplementation and Arginase Inhibition - Krause, Bernardo J.; Casanello, Paola; Dias, Ana C.; Arias, Paulina; Velarde, Victoria; Arenas, German A.; Preite, Marcelo D.; Iturriaga, Rodrigo (Frontiers in Physiology, 2018)
Chronic intermittent hypoxia (CIH), the main feature of obstructive sleep apnea (OSA), produces oxidative stress, endothelial dysfunction and hypertension. Nitric oxide (NO) plays a critical role in the regulation of the vasomotor tone. The NO level depends on the L-arginine availability, which can be reduced by arginase enzymatic activity, and its reaction with the superoxide radical to produce peroxynitrite. Accordingly, we hypothesized whether a combination of an arginase inhibitor and an antioxidant may restore the endothelial function and reduced arterial blood pressure (BP) in CIH-induced hypertensive rats. Male Sprague-Dawley rats 200 g were exposed either to CIH (5% O2, 12 times/h 8 h/day) or sham condition for 35 days. BP was continuously measured by radio-telemetry in conscious animals. After 14 days, rats were treated with 2(S)-amino-6-boronohexanoic acid (ABH 400 μg/kg day, osmotic pump), N-acetylcysteine (NAC 100 mg/kg day, drinking water) or the combination of both drugs until day 35. At the end of the experiments, external carotid and femoral arteries were isolated to measure vasoactive responses to KCl and acetylcholine (ACh) using wire-myography. The CIH-induced hypertension ( 8 mmHg) was reverted by ABH, NAC and ABH/NAC administration. Carotid arteries from CIH-exposed rats showed higher active contraction induced by KCl compared to sham rats (3.4±0.4 vs. 2.4±0.2 N/m2) and decreased ACh-induced relaxation (12.8±1.5 vs. 30.5±4.6%). ABH reverted the enhanced contraction (2.5±0.2 N/m2) and the impaired ACh-induced relaxation in CIH carotid arteries (38.1±4.9%). However, NAC did not revert the increased vessel contraction (3.9±0.6 N/m2) induced by KCl and failed to restore the impaired ACh-induced relaxation in carotid arteries (10.7±0.8%). Femoral arteries from CIH rats showed an increased contractile response, an effect partially reverted by ABH, but completely reverted by NAC and ABH/ NAC. The impaired endothelial-dependent relaxation in femoral arteries from CIH rats was reverted by ABH and ABH/NAC. In addition, ABH/NAC at high doses had no effect on liver and kidney gross morphology and biochemical parameters. Thus, although ABH, and NAC alone and the combination of ABH/NAC were able to normalize the elevated BP, only the combined treatment of ABH/NAC normalized the vascular reactivity and the systemic oxidative stress in CIH-treated rats.